Análise do financiamento da educação no município de Aracaju/SE (2013) - Xavier Neto, Lauro Pires (2017)
The formulation of this work took place during the political effervescence and the structural and intense crisis of the capitalist system of production. From the deliberate disarticulation of the union organization and the social movements, the advance of neoliberal policies, the idea withdrawal of hegemonic parties in search of establishing socialism and the possible historical moment of the rise of the masses, our central thesis is based on. It refers that only the process of radical social transformation can alter the Brazilian educational reality, including in it the primordial role of the revolutionary educational process that, within the formal school structure, it will only make sense if it is aimed at inciting the masses, denouncing and pointing out the system problems and being able to outrage the subjects involved in the educational daily life (professors, students, technical employees and the community), with the purpose of making them reflect on the possibility of engaging in a radical, universal and international process of social transformation. Our research problem questions how the public funds, in a municipality linked to a right-wing party (DEM - The Democrats), were being used and if, in fact, such resources were being allocated for the development of public education. Thus, we analyzed the educational policy of the Federal Government, its projects and programs, in order to find links with the demands guided by the capital. The objectives of this piece of research were: to verify the Brazilian social and educational reality; to analyze the financing educational policies of the municipality of Aracaju/SE; to understand the educational reality from the financing policies; to verify how a right- wing project (from the municipal manager´s party binding), in Aracaju / SE, acts so as to strengthen the dictates of the neoliberal policies; and to carry out an analysis of the financing in education in the Aracaju City Hall, in 2013. Our hypotheses indicated that the public resources of education in Aracaju/SE privileged and enhanced the private sectors. Regarding the method that guides the work, we opted for the historical and dialectical materialism from the Totality category. The adopted methodology was the analysis, from the data collected in the Portal da Transparência (Transparency Site) and in the TCE/SE (Accounting Court of the State of Sergipe), of all contracts, agreements, commitments and payments fulfilled in the surveyed municipality in 2013, and their relations with funds from the MDE (Maintenance and Development of Education), Education-Salary Law and FUNDEB (Fund for the Development and Maintenance of Elementary Education and Recognition of the Teaching Profession). We verified that, in Aracaju/SE, a considerable part of the educational funds was meant to the private initiative or to projects related to companies, weakening the res publica, and strengthening the neoliberal political projects, thus pointing out that the political and economic structure in Brazil does not favor an educational process aimed at social transformation, and a radical rupture must be achieved with this form of organization that is linked to the dictates and commercial and political interests of the capital.